Analysis of Efficiency and Effectiveness of The Performance of Public Housing and Residential Area: The case of Palembang - Dharmika, Sya'nia (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
Dinas Perumahan Rakyat dan Kawasan Permukiman (Pera KP) is an element of the Regional Apparatus Organization (OPD) of the regional government of Palembang City which operates in 4 (four) heads of fields, namely, the fields of Utilities, Environmental Sanitation, Housing and Environmental Roads. In 2018, there are several activities or programs that have not been realized but will be realized in 2019. This research identifies activities or programs in 2019 using the Efficiency and Effectiveness method. Based on the results obtained, the Pera KP Office is included in the Efficiency category. While the results of the questionnaire distributed using the Community Satisfaction Index, the effectiveness level was in the good category with a number of 68.5